Ecophysiology of Antarctic sea-ice meiofauna - Kiko, Rainer (2008)
Sea ice is permeated by small brine channels, which are characterised by sub-zero temperatures and varying salinities. Despite sometimes extreme conditions a relatively diverse fauna and flora thrives within these brine channels. Stephos longipes, Paralabidocera antarctica and Drescheriella glacialis are the dominant copepod species found within Antarctic sea ice. Their life-cycle strategies are well-established, but life cycles of other meiofauna (metazoans > 50 µm) found within sea ice are little explored. Adaptation mechanisms allowing meiofauna species to survive within sea ice are largely unknown. In order to increase our knowledge of the Antarctic sea-ice meiofauna, different microhabitats of sea ice and their metazoan fauna were studied during two cruises with R/V “Polarstern” to the western Weddell Sea. The dominant sympagic copepod species found in the sub-ice layer was Ectinosoma sp., other sympagic copepod species occurring regularly were D. glacialis/racovitzai, Diarthrodes cf. lilacinus, Idomene antarctica and S. longipes. Drescheriella glacialis/racovitzai and Stephos longipes were the dominant members of the surface-layer meiofauna during late spring. Their populations consisted mainly of adults and early naupliar stages in this layer, which points to an active reproduction of these species within the surface layer. Other taxa found in the surface layer were undetermined turbellarians, the gastropod Tergipes antarcticus, a ctenophore and two amphipod species. Sampling records from the Bellingshausen Sea, the Weddell Sea, as well as from the Prydz and the Lützow-Holm Bay indicate that T. antarcticus is widely distributed in Antarctic sea ice. During this study, adults, juveniles, veliger larvae and egg clutches of T. antarcticus were found in sea ice. A thorough morphological and anatomical description of all life stages was performed and the developmental time from egg to veliger larvae was determined as being 31 days (range: 13 to 65 days) at 0 °C. The observed reproduction of D. racovitzai, ...